BAHASA KIASAN, GAYA BUNYI, DAN SAJAK DALAM LIRIK LAGU ALBUM 'PEJANTAN TANGGUH' KARYA SHEILA ON 7 - Rahmaditya Khadifa Abdul Rozzaq Wijaya (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2021)
This research was aimed at finding and describing the functions of figurative languages, sound styles, and rhymes and in the song lyrics of Sheila on 7 from the album Pejantan Tangguh. This is descriptive-qualitative research whose data are words, phrases, and sentences of the song lyrics in in the album. For collecting the data, Â the researcher applied listening-and-note-taking method whereas for analyzing the data, referential comparative method was employed by determining element selection technique. The results showed that frequent sound styles appears in the lyrics are asonancy and alliteration. This asonancy was used to produce combinations of rhythms that resulted in beautiful effects in the song. Meanwhile, the most dominant figurative language found in the lyrics was metaphor which is followed by personificationm, and hyperbole. All the positions of rhymes, from beginning, middle, to end can also be found in the lyrics.